COMMUNITY PARTICIPATION IN ASSISTANCE OF CHILDREN CRIMINAL ACTORS - Shinta Rukmi Budiastuti; Waluyo Pradoto; Agatha Jumiati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
In order to handle children in conflict with the law, the public must be directly involved in enforcing criminal law, so that they can judge whether the criminal case settlement process can bring justice or not and participate through an institution that oversees the implementation of the criminal justice system. The purpose of this study was to determine and analyze the extent of community participation in assisting children who commit crimes so that it can help reduce trauma to create a good future for children. This research is used to find a model of community participation in mentoring children who commit crimes based on primary data and secondary data This community participation is a new breakthrough in the model of assisting children in conflict with the law, in order to reduce the trauma caused by the imposition of criminal sanctions. Children get a better life after serving a criminal period so that they can manifest their self-confidence to return to society Keyword: children, criminal law, cummunity participation